The known unknowns: understanding slow-growing bacteria and their plant interaction through reverse ecology approaches - Gonçalves, Osiel Silva (Universidade Federal de Viçosa, 2023)
The cultivation of bacteria that exhibit slow growth rates has posed a longstanding challenge in microbiology, resulting in a significant number of unculturable bacterial species. This phenomenon, known as the "great plate count anomaly", represents one of the oldest unresolved topics in the field. Recent advancements in cultivation techniques have shown promise in overcoming this challenge. In addition, the study of slow-growing bacteria and their interactions with plants has gained significant attention due to their ecological importance and potential applications in agriculture. Genomics techniques have provided valuable insights into the genetic characteristics underlying microbe-plant interactions. In this context, by examining the in-cultivation techniques, genomics, and computational modeling, we seek to shed light on the slow-growing bacteria and uncover their contributions to ecosystem functioning and plant interaction. Our initial understanding was obtained through the study of 92 slow-growing bacteria isolated from the Brazilian Cerrado soil during a four week-long isolation period. These bacteria can thrive in low-water conditions, promote plant growth, and belong to a novel species group. Genome analysis of five strains revealed their potential in biogeochemical cycles, plant growth promotion, and biosynthesis of secondary metabolites. Next, we conducted greenhouse experiments to assess the efficacy of these bacteria in soybean cultivation, employing a carefully designed bacterial consortium based on our comprehensive understanding of microbial-microbe and plant-microbe interactions. The results showed promising outcomes for improving soybean productivity. In the third chapter of this thesis, we employed in-silico modeling to design a synthetic microbial community aimed at enhancing the yield of important crop plants. By selecting six hub species with essential plant growth-promoting traits from the dominant plant species found in the Campos rupestres, we aimed to optimize the plant-microbe interactions and maximize crop productivity. Lastly, our analysis of 758 metagenome- assembled genomes shed light on the global distribution of the Acidobacteriota phylum and its interactions with plants and biogeochemical processes. This exploration revealed distinct ecological roles for individual taxonomic groups within this phylum, providing valuable insights for future research. Overall, our thesis contributes to a better understanding of slow-growing bacteria, their ecological significance, and their potential applications in agriculture, offering insights into ecosystem functioning and plant interactions. Keywords: Agriculture. Slow-growing bacteria. Ecosystems. Genomics. Microbe-plant interactions. Microbiology

O cultivo de bactérias de crescimento lento tem sido um desafio persistente na área da microbiologia, resultando em muitas espécies bacterianas que não podem ser cultivadas. Esse fenômeno, conhecido como "a grande anomalia na contagem de placas", é um dos problemas mais antigos não resolvidos na microbiologia. Recentemente, foram feitos avanços nas técnicas de cultivo que têm mostrado promessa para superar esse desafio. Além disso, o estudo das bactérias de crescimento lento e suas interações com as plantas tem recebido atenção significativa devido à sua importância ecológica e às possíveis aplicações na agricultura. A genômica tem fornecido informações valiosas sobre as características genéticas que estão por trás dessas interações entre microrganismos e plantas. Nesse contexto, examinamos as técnicas de cultivo, a genômica e a modelagem computacional para esclarecer as bactérias de crescimento lento e descobrir como elas contribuem para o funcionamento dos ecossistemas e para a interação com as plantas. Nosso primeiro entendimento foi obtido por meio do estudo de 92 bactérias de crescimento lento isoladas do solo do Cerrado. Essas bactérias têm a capacidade de se desenvolver em condições com pouca água, características promissoras para promover o crescimento das plantas, e pertencem a um novo grupo de espécies. A análise do genoma de cinco linhagens revelou seu potencial em ciclos biogeoquímicos, promoção do crescimento das plantas e biossíntese de metabólitos secundários. Em seguida, realizamos experimentos em casa de vegetação para avaliar a eficácia dessas bactérias no cultivo da soja, utilizando um consórcio bacteriano cuidadosamente projetado, com base nas interações microbianas e com as plantas. Os resultados se mostraram promissores para melhorar a produtividade da soja. No terceiro capítulo da tese, utilizamos a modelagem in-silico para projetar uma comunidade microbiana sintética com o objetivo de aumentar o rendimento de importantes plantas agrícolas. Selecionamos seis espécies centrais com características essenciais para a promoção do crescimento das plantas, a partir das espécies dominantes encontradas nos Campos rupestres, buscando otimizar as interações entre micróbios e plantas e maximizar a produtividade de importantes culturas agrícolas. Por fim, nossa análise de 758 genomas montados a partir de metagenomas trouxe novas informações sobre a distribuição global do filo Acidobacteriota e suas interações com plantas e processos biogeoquímicos. Essa exploração revelou papéis ecológicos distintos para grupos taxonômicos individuais dentro desse filo, fornecendo informações valiosas para pesquisas futuras. Em resumo, essa tese contribui para uma melhor compreensão das bactérias de crescimento lento, sua importância ecológica e suas possíveis aplicações na agricultura. Além disso, ela oferece informações valiosas sobre o funcionamento dos ecossistemas e as interações entre micróbios e plantas. Palavras-chave: Agricultura. Bactérias de crescimento lento. Ecossistemas. Genômica. Interações micróbio-planta. Microbiologia.
Desconhecidos conhecidos: compreendendo as bactérias de crescimento lento e suas interações com as plantas através de abordagens de ecologia reversa
Keywords: Bacteriologia - Cultura e meios de cultura; Microbiologia; Ecossistemas; Genômica; Agricultura; Microbiologia Agrícola